Cherenkov radiation energy transfer from [18F]-fluorodeoxyglucose to subphthalocyanine fluorophores - Lioret, Vivian; Decréau, Richard A. (Comptes Rendus. Chimie)
Cherenkov radiation (CR) is an optical light that is emitted during the decay of beta-particle-emitting radionuclides, such as 18F, which is present in [18F]-fluorodeoxyglucose, a well-known tracer used in positron emission tomography. The CR emission occurs from relaxation of molecules of the dielectric medium surrounding the emitted beta-particle. The Cherenkov radiation energy transfer (CRET) to a CR acceptor, such as subphthalocyanine, was analyzed. Subphthalocyanine is a unique concave-shaped 14π-electron fluorophore with optical properties. The relevance of such a CR emitter/acceptor couple to performing CRET is discussed.